Developing Bilingual Narrative Writing Materials Based on Local Wisdom “Antara Lepet dan Sura” to Enhance Students’ Writing Proficiency and Bilingualism - Tria Oktafia; Junaedi Setiyono; Titi Rokhayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
This study aims to develop bilingual narrative writing materials based on local wisdom through the short story Antara Lepet dan Sura to enhance students’ writing proficiency, bilingual competence, and cultural awareness. The research employed a Research and Development (R&D) approach using the Dick and Carey instructional design model, which includes systematic stages of analysis, design, development, evaluation, and revision. The study was conducted at SMK Pancasila 1 Kutoarjo, involving 20 eleventh-grade students, two English teachers, and one lecturer as expert validators. Data were collected through questionnaires, interviews, and documentation, and analyzed using both quantitative and qualitative methods. Quantitative analysis using Pearson Product-Moment correlation revealed that all instrument items were valid (r-count > 0.433), while reliability testing showed a high Cronbach’s Alpha coefficient (α = 0.905), indicating excellent internal consistency. Qualitative findings from expert validation and user responses indicated that the developed materials are pedagogically appropriate, culturally relevant, and effective in supporting bilingual narrative writing. The integration of Central Javanese local wisdom enhanced students’ motivation, creativity, and understanding of narrative structure, while also strengthening their cultural identity. The findings demonstrate that the developed materials are valid, reliable, and effective for classroom implementation. Therefore, the bilingual narrative writing module based on Antara Lepet dan Sura can be recommended as an innovative and contextually grounded instructional resource for vocational high school English learning, with strong potential for further development in digital and broader educational contexts.